FORMULASI PENGATURAN PIDANA SEUMUR HIDUP DALAM SISTEM HUKUM NASIONAL - Sukarno, Sukarno (Jurnal Muhakkamah, 2019)
Indonesian criminal law specifically contained in the Criminal Code is based on historical, political, and sociological reasons. Reform (supporting the new KUHP concept) needs to be done to pay attention to the legal values ​​that live in the community, including the Imposition of Life Prison. Such understanding should be the basis for consideration in discussing the existence of life sentence victims. The results of the study showed that the position and regulation of life imprisonment were not explicitly stated (explicitly) regulated in the composition of the criminal (criminal code) in Article 10 of the Criminal Code, but life imprisonment was included in Article 12 paragraph (1) of the Criminal Code. Besides that, the formulation of the forms of visible criminal threats are (1) life imprisonment which is always normalized with 20 years of imprisonment, while in the position of life imprisonment outside the Criminal Code using an alternative system of cumulation.